2022
DOI: 10.1002/essoar.10510005.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Net primary production and ecosystem carbon flux of Brazilian tropical savanna ecosystems from eddy covariance and inventory methods

Abstract: Estimates of net primary (NPP) and ecosystem production (NEP) are needed for tropical savanna, which is structurally diverse but understudied compared to tropical rainforest. Estimates of NPP and NEP are available from eddy covariance and inventory methods, but both approaches have errors and uncertainties. We used both methods to estimate carbon (C) fluxes for an upland mixed grassland and a seasonally flooded forest to determine the correspondence in C cycling components derived from these

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Researchers used the EC and inventory methods to estimate carbon fluxes in upland mixed grasslands and seasonally flooded forests. The results showed that the estimates of carbon fluxes obtained by the two methods were essentially identical [40].…”
Section: Methods Of Observationmentioning
confidence: 85%
“…Researchers used the EC and inventory methods to estimate carbon fluxes in upland mixed grasslands and seasonally flooded forests. The results showed that the estimates of carbon fluxes obtained by the two methods were essentially identical [40].…”
Section: Methods Of Observationmentioning
confidence: 85%
“…Eddy covariance and meteorological data for the Cerrado forest at Baia das Pedras (Brazil‐Northern Pantanal Wetland: BR‐Npw) is available through Ameriflux (https://ameriflux.lbl.gov/sites/siteinfo/BR-Npw). Data used in this paper, and selected formulas, are available on Mendeley (https://data.mendeley.com/) under the citation: Vourlitis, George (2021a), “Net primary production and ecosystem carbon flux of Brazilian tropical savanna ecosystems from eddy covariance and inventory methods”, Mendeley Data, V1, doi: http://10.17632/kcwwktkd85.1.…”
Section: Data Availability Statementmentioning
confidence: 99%